Whistleblowing mechanism: what factors make it effective? - Putu Wira Dharma; Agus Fredy Maradona (Universitas Merdeka Malang, 2025)
Fraud cases have become a serious and global problem that has a wide impact on various sectors, including the government sector. Fraudulent practices in public institutions not only harm the state financially but also weaken public trust in government institutions. One of the preventive efforts that is now widely developed is the implementation of the Whistleblowing mechanism, namely a reporting system that allows individuals to report unethical or illegal actions without fear of retaliation. This study aims to analyze the effectiveness of the implementation of the Whistleblowing mechanism in the Klungkung Regency Government using the whistleblowing Triangle approach, which includes three main elements: opportunity, pressure, and rationalization. This study uses a qualitative method with data collection techniques through in-depth interviews with related officials, field observations, and analysis of internal policy documents. Data were analyzed using NVivo software to identify key themes and emerging patterns. The results of the study indicate that although the whistleblowing system has been formally established, its effectiveness is still hampered by low motivation of reporters, lack of protection for reporters, and minimal trust in the available mechanisms. This study recommends improving the reporting system, strengthening regulations for protecting whistleblowers, and internalizing integrity values to strengthen transparency and accountability in the public sector, especially in the Klungkung Regency Government